Answer:
Explanation:
1) 4 (2x+3)=1
(42x)*43= 1
64*42x=1
Taking Log to the base 2 to solve
log2(64*42x)
By property of ln
log2 (xy)= log2 x + log2 y
Therefore,
= log2 (64)+ log2 (42x)
log2 (64) =6 and by Property log2 (xn) = n logb x.
= 6 + 2x log2 4
= 6 + 2x (2)
Putting above equation equal to 0 to get the value of x
6 + 4x = 0
4x = -6
x = - 6/4
x= -3/2
Putting value of x in given equation
(42x)*43= 1
64 * 4(2*(-3/2)) =1
43 * 4-3 = 1
64/64 =1
1=1
2) 81 * 9(-2b-2) = 27
81 * 9-2b * 9-2 = 27
9-2 = 81
(81/81) * 9-2b =27
9-2b = 27
(32)-2b = 33
3-4b = 33
-4b=3
b= -3/4
Putting b’s value in given equation
81 * 9(-2b-2) = 27
81 * 9((-2*-3/4)-2) =27
(81/81) * 9 3/2 = 27
9 3/2 = 27
27 = 27
3) 31-2x = 243
3 * 3-2x =243
3-2x =243/3
3-2x = 81
3-2x = 34
-2x = 4
x = -2
putting the value of x in given equation
31-2(-2) = 243
31+4= 243
35= 243
243 =243
4) 43X-2 = 1
43X * 4-2 = 1
43X / 42 = 1
43X / 16 = 1
43X = 16
3x = 2
X=2/3
Putting value of x in given equation
4(3*2/3)-2 = 1
42-2 =1
40 =1
1=1
5) (1/6) (3x+2) * 216 3x = 1/216
216 = 63
6 (-3x-2) * 216 3x = 1/216
6 (-3x) * 6-2 * 216 3x = 1/63
6 (-3x) * (63)3x = 6-3/6-2
6 (-3x) * 69x = 6-3 * 62
69x-3x = 6(-3+2)
66x = 6-1
6x = -1
x=-1/6
Putting value of x in given equation
(1/6) (3*-1/6+2) * 216 3*-1/6 = 1/216
(1/6) (-1/2+2) * 216 -1/2 = 1/216
(1/6) ((-1+4)/2) * 216 -1/2 = 1/216
(1/6) (3/2) * (63)-1/2 = 1/216
6-3/2 * 6-3/2 = 1/216
6 (-3/2-3/2) = 1/216
6 (-6/2) = 1/216
6 (-3) = 1/63
6 (-3) =6 (-3)